Catalpol protects against 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin‐induced cytotoxicity in osteoblastic MC3T3‐E1 cells. Issue 12 (19th August 2019) - Choi, Eun Mi; Suh, Kwang Sik; Jung, Woon‐Won; Yun, Soojin; Park, So Young; Chin, Sang Ouk; Rhee, Sang Youl; Chon, Suk
Abstract: 2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin (TCDD) is a well‐known environmental contaminant that produces a wide variety of adverse effects in humans. Catalpol, a major bioactive compound enriched in the dried root of Rehmannia glutinosa, is a major iridoid glycoside that alleviates bone loss. However, the detailed mechanisms underlying the effects of catalpol remain unclear. The present study evaluated the effects of catalpol on TCDD‐induced cytotoxicity in osteoblastic MC3T3‐E1 cells. Catalpol inhibited TCDD‐induced reduction in cell viability and increases in apoptosis and autophagic activity in osteoblastic MC3T3‐E1 cells. Additionally, pretreatment with catalpol significantly decreased the nitric oxide and nitrite levels compared with a control in TCDD‐treated cells and significantly inhibited TCDD‐induced increases in the levels of cytochrome P450 1A1 and extracellular signal‐regulated kinase. Pretreatment with catalpol also effectively restored the expression of superoxide dismutase and extracellular signal‐regulated kinase 1 and significantly enhanced the expression of glutathione peroxidase 4 and osteoblast differentiation markers, including alkaline phosphatase and osterix. Taken together, these findings demonstrate that catalpol has preventive effects against TCDD‐induced damage in MC3T3‐E1 osteoblastic cells. Abstract : Catalpol inhibited TCDD‐induced reduction in cell viability and increases in apoptosis and autophagic activity in osteoblastic MC3T3‐E1 cells. Additionally, pretreatment with catalpol significantly decreased the NO and nitrite levels compared to a control in TCDD‐treated cells and significantly inhibited TCDD‐induced increases in the levels of CYP1A1 and ERK. Pretreatment with catalpol also effectively restored the expression of SOD and ERK1 and significantly enhanced the expression of GPx4 and osteoblast differentiation markers, including ALP and Osterix.